Post-Harvest Storage and Processing Technology in Russia: Reducing Yield Loss - Gareev Ozal; Chekhonin Ilyasova; Vladimir Ilgiz (Yayasan Adra Karima Hubbi, 2024)
The background of the study is based on the high rate of postharvest agricultural yield loss in Russia, which has had a significant impact on the country's food security and agrarian economy. This yield loss is due to the need for adequate storage and processing technology, thereby shortening the shelf life of farm products and degrading the quality of the crop. This study aims to evaluate the effectiveness of various postharvest storage and processing technologies in reducing agricultural yield losses in Russia. This research method uses a quantitative approach with primary and secondary data collection. Primary data were obtained through surveys and interviews with farmers and agronomists in different agricultural regions of Russia. Secondary data are collected from official reports, scientific journals, and related publications. Data analysis was carried out using statistical techniques to measure the impact of storage and processing technologies on yield loss rates and the quality of agricultural products. The results showed that applying cold storage, drying, and vacuum packaging technologies significantly reduced agricultural yield losses by up to 30% compared to conventional methods. In addition, this technology also improves the quality and shelf life of agricultural products, thereby expanding market reach and increasing farmers' incomes. The study also found that adopting this technology still needs to be improved in some areas due to a lack of knowledge and high initial investment. The study's conclusion shows that postharvest storage and processing technologies have great potential to reduce agricultural yield losses in Russia. To achieve maximum benefits, awareness-raising and training for farmers and investment support from the government and the private sector are needed. Thus, the application of this technology can contribute significantly to food security and the improvement of the welfare of farmers in Russia.